Sound-activated mobile game - Gwee, Jia Xiang (Nanyang Technological University, 2024)
This paper introduces a sound-activated mobile game designed to engage users through interactive and intuitive gameplay. Unlike conventional mobile games which utilise touch or motion sensors, this innovative game wields sound as its primary input mechanism. Through the use of a mobile device’s microphone, the game detects and responds to various sound frequencies and amplitudes. With the help of machine learning, ambient noise can be transformed into actionable gameplay elements. Players will navigate through obstacles and overcome challenges by making specific sounds either through controlling their environment acoustically or with bodily actions such as clapping or knocking. The novelty and creativity of these sound-based controls are generally appreciated among playtesters, recognising their potential to enhance engagement and immersion. While the game does push the boundaries of interactive entertainment, refining the accuracy and consistency of the sound detection will be vital to maximising player satisfaction and ensuring sustained engagement over time